2019
DOI: 10.1002/jper.19-0043
|View full text |Cite
|
Sign up to set email alerts
|

Poor oral hygiene is associated with the detection of obligate anaerobes in pneumonia

Abstract: Background Oral cavity is a reservoir of various respiratory pathogens, and poor oral hygiene is associated with an increase in anaerobic bacteria in oral cavity. In addition, it positively relates higher risk of developing pneumonia and increased pneumonia‐related mortality. However, the association between poor oral hygiene and increase in obligate anaerobes in the lungs of pneumonia patients is unclear. Methods A total of 39 patients with pneumonia in whom bronchoscopic examination and oral hygiene evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 31 publications
(43 reference statements)
2
16
0
Order By: Relevance
“…30 Recently, the 16S ribosomal RNA (rRNA) gene of microorganisms has been analyzed, and it was found that anaerobes are more frequently detected in patients with pneumonia than reported using conventional culture methods. 31,32 Furthermore, we reported previously that the presence of bacteria in the mesenteric lymph nodes during surgery and in the blood on POD 1 strongly predicted the 5-6. Pneumonia present at the time of the CT evaluation was defined as early-onset pneumonia, and pneumonia that developed after the CT scan was defined as late-onset pneumonia occurrence of postoperative pneumonia after esophagectomy, and the bacteria detected were predominantly obligate anaerobes.…”
Section: Discussionmentioning
confidence: 88%
“…30 Recently, the 16S ribosomal RNA (rRNA) gene of microorganisms has been analyzed, and it was found that anaerobes are more frequently detected in patients with pneumonia than reported using conventional culture methods. 31,32 Furthermore, we reported previously that the presence of bacteria in the mesenteric lymph nodes during surgery and in the blood on POD 1 strongly predicted the 5-6. Pneumonia present at the time of the CT evaluation was defined as early-onset pneumonia, and pneumonia that developed after the CT scan was defined as late-onset pneumonia occurrence of postoperative pneumonia after esophagectomy, and the bacteria detected were predominantly obligate anaerobes.…”
Section: Discussionmentioning
confidence: 88%
“…This is probably because the standard of dryness was strict (score = 2 by OHAT). Because the relationship between oral dryness and pneumonia was reported previously [20], we paid attention only when considering a review of the standards. In addition, we found that the older patients needed more extensive oral management.…”
Section: Discussionmentioning
confidence: 99%
“…45 In a study using the clone library analysis of bronchoalveolar lavage fluid, the phylotypes of oral streptococci and obligate anaerobes were detected in 79.5% and 66.7% aspiration pneumonia patients, respectively. 46 Oral hygiene level was inversely correlated with the detection of the phylotypes.…”
Section: Tong Ue Cle Aning For Removing Tong Ue Coatingmentioning
confidence: 97%